2006
DOI: 10.1158/1078-0432.ccr-06-0449
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Expression of Stem Cell Factor Bmi1 in Precancerous Lesions of the Gastrointestinal Tract

Abstract: Purpose: It is important to identify the definitive molecular switches involved in the malignant transformation of premalignant tissues. Cellular senescence is a specific characteristic of precancerous tissues, but not of cancers, which might reflect tumorigenesis-protecting mechanisms in premalignant lesions. Polycomb protein Bmi1, which is a potent negative regulator of the p16INK4 gene, suppresses senescence in primary cells and is overexpressed in various cancers. We hypothesized that Bmi1 expression would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
49
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 50 publications
(42 reference statements)
10
49
0
Order By: Relevance
“…Bmi1 is involved in self-renewal in haematopoietic and neuronal cells (Lessard and Sauvageau, 2003;Molofsky et al, 2003). In addition, Bmi1 expression is dysregulated in preneoplastic colorectal epithelium and overexpression correlates with malignant progression (Tateishi et al, 2006), supporting a role for Bmi1 in human colorectal cancer progression. Previous studies have shown that HRA-19 cells, which have a low inherent tumourigenicity, acquired a 100% take rate in xenografts when embedded in type I collagen gel (Del-Buono et al, 1991), suggesting a functional significance to colon cancer cell -collagen interactions.…”
Section: Discussionmentioning
confidence: 94%
“…Bmi1 is involved in self-renewal in haematopoietic and neuronal cells (Lessard and Sauvageau, 2003;Molofsky et al, 2003). In addition, Bmi1 expression is dysregulated in preneoplastic colorectal epithelium and overexpression correlates with malignant progression (Tateishi et al, 2006), supporting a role for Bmi1 in human colorectal cancer progression. Previous studies have shown that HRA-19 cells, which have a low inherent tumourigenicity, acquired a 100% take rate in xenografts when embedded in type I collagen gel (Del-Buono et al, 1991), suggesting a functional significance to colon cancer cell -collagen interactions.…”
Section: Discussionmentioning
confidence: 94%
“…Despite these substantive advances in mice, limited progress has been made regarding the assessment of candidate ISC markers in humans. Conflicting data exist on BMI1 mRNA and protein expression in human small and large intestine (9)(10)(11), and systematic assessment of LGR5, ASCL2, and OLFM4 is hindered by a lack of appropriate antibodies and has been limited to surrogate in situ hybridization studies. OLFM4 is perhaps the best studied candidate in humans, showing mRNA expression at the crypt base throughout the intestinal tract (12).…”
Section: Introductionmentioning
confidence: 99%
“…7 PcG proteins are part of the conserved cellular memory system that prevents changes in cell identity by repressing the transcriptional state of several loci in the genome. Bmi1 is overexpressed in several carcinomas, [7][8][9][10][11] including liver carcinoma. 12 Polycomb-Repressive Complex 2 (PRC2) members, for example EZH2, are also associated with cancer 9,13,14 and several studies have shown that EZH2 is highly expressed in aggressive prostate and breast carcinomas.…”
mentioning
confidence: 99%